The Augment Use of Εειπε and Ειπε in Early Epic Greek: An Evidential Marker?. Issue 1 (1st January 2018) - De Decker, Filip
Abstract : This article is part of an ongoing investigation into the meaning, origin and use of the augment in Early Greek prose and poetry and discusses the use and absence of the augment in the forms of the simplex ἔειπον/εἶπον in early epic Greek (Homer, Hesiod and the Homeric Hymns). I first explain why this verb was chosen and then proceed to determining the corpus. I start by listing the criteria to determine which forms are metrically guaranteed; when a form is not secured by the metre, I use the "Barrett–Taida" method, which analyses metrically insecure forms by comparing them to the metrically secure forms of the same paradigm and to the attestations and positions in the verse. The corpus that is thus established is then analysed by using previous scholarship on syntactic constraints (Drewitt–Beck's clitic rule and Kiparsky's "conjunction reduction" rule) and on the semantics (Koch–Basset's distinction of narrative versus speech and Platt–Bakker–Mumm's theory of recent past versus Hoffmann's remote and timeless past); special attention is also paid to the exceptions. At the end, I investigate if the augment use in epic Greek can be explained as a visual evidential marker.